PENGARUH PERENCANAAN PAJAK, PROFITABILITAS, BEBAN PAJAK TANGGUHAN DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN NON MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Ayu Via Fitriya; Maslichah Maslichah; M. Cholid Mawardi (Universitas Islam Malang, 2020)
ABSTRACTThis study aims to examine the empirical evidence as to which effect the tax planning, profitability, deferred tax burden and size of the firm on the earnings management. This method uses quantitative methods. The population in this study is non-manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018.The sample selection uses purposive sampling. A sample of 100 companies with three years of observation, so that the total test sample is 300 observations. The type of data uses secondary data, data analysis uses multiple linear regression, normality test, classic assumption test and hypothesis test.The results of this study indicate that the partial hypothesis of tax planning, profitability, deferred tax burden has a significant effect on earnings management while company size has no significant effect on earnings management. For simultaneous testing between tax planning, profitability, deferred tax expense and company size have an influence on earnings managementKeywords: Tax Planning, Profitability, Deferred Tax Burden, Company Size, and Earning Management.